PrintSense: A Versatile Sensing Technique to Support Multimodal Flexible Surface Interaction - Gong, Nan-Wei; Steimle, Jürgen; Olberding, Simon; Hodges, Steve; Gillian, Nicolas; Kawahara, Yoshihiro; Paradiso, Joseph A. (Proceedings of CHI 2014, 2014)
We present a multimodal on-surface and near-surface sensing technique for planar, curved and flexible surfaces. Our technique leverages temporal multiplexing of signals coming from a universal interdigitated electrode design, which is printed as a single conductive layer on a flexible substrate. It supports sensing of touch and proximity input, and moreover is capable of capturing several levels of pressure and flexing. We leverage recent developments in conductive inkjet printing as a way to prototype electrode patterns, and combine this with our hardware module for supporting the full range of sensing methods. As the technique is low-cost and easy to implement, it is particularly well-suited for prototyping touch- and hover-based user interfaces, including curved and deformable ones.